Designing Performance Measurement System Of Pt Kidang Kencana Sakti By Using Balanced Scorecard - Agung Widyaprakoso Winardi; Budi Sulistyo; Ima Normalia Kusmayanti (eProceedings of Engineering, 2019)
Abstract PT. Kidang Kencana Sakti is a company engaged in the gas turbine maintenance services. This company employed performs a financial aspect to evaluate company’s performance. However, this is unable to control the company’s operational process,customers, and learning and growth. Therefore, it is necessary to create a measurement tool that is in line with the vision and mission of the company. This study aims to develop a balanced scorecard to measure the company’s performance. The final result of this final project is determine the strategies based on the company’s vission and mission, to determine the performance indicators. The weighting of each indicator for financial perspective is 31%, customer perspective is 45%, internal business process perspective is 15%, learning and growth perspective is 9%. The highest weighting score is the customer perspective. Keywords – Balanced Scorecard (BSC), Analytical Hierarchy Process (AHP), Performance Measurement